Prevalencia y factores asociados a embarazo reincidente en adolescentes que acuden a C.S. Carlos Showing Ferrari 2013 - Ramirez Montalvo, Rosalinda (2017)
Objective. To determine the prevalenceandfactors associated withteenage pregnancyrecidivist. Methods. A descriptive study of 73 adolescent relational in gestation took place, from the CS Showing Carlos Ferrari, Amarilis District, Huanuco Department, during the period 2013. In the collection of the data, a survey form was used. For the inferential analysis the Chi square test was used. Results. Of all teenage pregnancies, 12.3% (9 teenagers) had recurrent pregnancy and among the factors significantly related to marital status found unbound (P ≤ 0.000), age less than 15 years of first sexual intercourse (P ≤ 0.000), age younger than 15 years of first pregnancy (P ≤ 0.003); separated parents (P ≤ 0.013) and history of teen pregnancy in the family (P ≤ 0.005). Conclusions. Individual, family and reproductive factors related to the occurrence of recurrent pregnancy attending adolescents in CS Showing Carlos Ferrari.